Prevalência de sintomas depressivos e fatores associados em idosas ativas e sedentárias : Subprojeto Rede Fibra - Martins, Isabella Carraro (2016)
The active lifestyle is related to the maintenance of health, prevention and care of depression in the elderly. Objective: To investigate the prevalence of depressive symptoms and associated factors in active and sedentary elderly women FIBER Network Project. Methods: Cross-sectional study sample of 460 older, with 211 active and 249 sedentary, aged 65 or more. Were used Geriatric Depression Scale (GDS), Daily Life Instrumental Activities (IADL), Mini Nutritional Assessment (MNA), body mass index, use of drugs, wages received, hand grip strength, walking speed and single leg balance. normality by Kolmogorov-Smirnov, ODSs Ratio (OR), fischer exact test and multiple linear regression coefficient was calculated. Results: We classified the GDS with severe and mild depression 3:47 of active, 10 and 101 sedentary respectively. The GDS in active elderly women presented OR of 3.3 for malnutrition and risk of malnutrition, 5.1 for perceived health very bad, bad and regular, 4.2 to have two or more comorbidities. In sedentary OR of 2.6 for perceived health and OR 3.0 to have two or more comorbidities. Low score in IADL correlated with depression between active and sedentary elderly. The low score on MAN was correlated with depression only in the active. Conclusion: The physical condition, nutritional status and increasing the number of comorbid conditions are worsening factors for depression. Being active and reeducate food are preventive measures of depression that should begin in adulthood.